Do huge waves exist in horizontal gas-liquid pipe flow?. (November 2017) - Parsi, Mazdak; Azzopardi, Barry J.; Al-Sarkhi, Abdelsalam; Kesana, Netaji R.; Vieira, Ronald E.; Torres, Carlos F.; McLaury, Brenton S.; Shirazi, Siamack A.; Schleicher, Eckhard; Hampel, Uwe
Highlights: CFD simulation is performed to explore the inception mechanism of periodic liquid structures in multiphase flow. Wire-Mesh Sensor is employed to investigate interfacial structures within the churn and pseudo-slug flow regimes. Huge waves of churn flow are compared to pseudo slugs. Abstract: Huge waves are periodic interfacial structures which are observed in vertical co-current gas-liquid two-phase flow under churn and the transition between churn and annular flows. Published data examining vertical gas-liquid flow indicate that a huge wave has either a continuous gas core surrounded by a large-scale interfacial wave or a core with a highly-agitated mixture of gas and liquid. Employing a Wire-Mesh Sensor (WMS), the spatio/temporal investigation of high flow rate horizontal air-water flow divulged some recurrent liquid structures (one may call pseudo-slugs) analogous to huge waves of (vertical) churn flow. In both cases, the blow-through (penetration of gas into the liquid structure) was the most manifest feature. Different qualitative and quantitative methods were employed to compare the behavior of pseudo-slug to churn flow. The quantitative measures included Probability Density Function analysis (PDF), distribution coefficient in drift flux model, structural velocity, core average velocity, interfacial friction factor, and slippage number. Both flow regimes demonstrated similar behavior. Graphical abstract: